An Afrocentric Revisit of Zuma led South Africa-China Relations, 2013-2017: Mutually Beneficial or Not - Dominic Maphaka (African Journal of Political Science)
Zuma’s administration remains the subject of scholarly debate and critics with many sections of the South African society calling it a nine wasted years. South Africa-China relations deepened largely during Zuma’s administration, specifically between 2013 and 2017. While the question of whether the relationship is mutually beneficial received large scholarly attention, the interrogation of this research phenomenon has not received attention from an Afrocentric lens. In view of the above, the current article revisits South Africa-China relations during Zuma’s administration to identify the benefits and challenges brought by the relationship using an Afrocentric perspective. In so doing, the article looks at South Africa-China cooperation in areas as cultural and academic exchange, financial trade, wildlife conservation and tourism. Methodologically, this a desktop qualitative article that relied heavily on secondary data and the collected data is analysed through discourse, and document analysis.